Keeping human rights in mind: embedding the Victorian Charter of Human Rights into the public mental health system. Issue 1 (2nd January 2021) - Katterl, Simon; Maylea, Chris
ABSTRACT: Despite aims to create a progressive inter-institutional dialogue about human rights, the Charter of Human Rights and Responsibilities 2006 (Vic) (Charter) has largely fallen flat. This becomes clearest when examining the failure of governments, regulators and services to comply with and properly consider rights when providing public mental health services. By failing to embed human rights in relevant policy levers, institutional and service design processes and workforce initiatives, the Charter bears little relevance to the day-to-day operation of the clinical mental health system. This paper argues that existing obligations on public authorities require a more systematic integration of human rights into the mental health system. In particular, it highlights the importance of Charter implementation into systems monitoring, service commissioning, regulatory oversight, service models of care, clinical governance frameworks and workforce development.